2018
DOI: 10.17221/99/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Chinese yellow cattle PPARA gene: Analyses of expression, polymorphism and trait association

Abstract: Peroxisome proliferator-activated receptor alpha (PPARA) is a member of the nuclear receptor superfamily that regulates key proteins involved in fatty acid oxidation and extracellular lipid metabolism. Given the importance of PPARA in modulating energy metabolism, PPARA may be a suitable candidate gene for assessing economic traits in cattle. In the present study, the genetic diversity of the PPARA gene in Chinese cattle breeds and its effects on growth traits in the Nanyang and Jiaxian breeds were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Results from recent studies have implicated that activation of Peroxisome proliferator-activated receptors associated with the regulation of lipid metabolism and alleviation of inflammation triggers hypolipidemic activities via acting on gene expression involved in lipid homeostasis [19] . There is emerging evidence that PPARα, a positive regulator of lipolysis connected with fatty acid oxidation and extracellular lipid metabolism, has ability to regulate the lipolysis of very low-density lipoproteintriglycerides (VLDL-TG), thereby raising plasma HDL-C levels and decreasing the levels of LDL-C and TG [19,20] . On the other hand, CYP7A1, as a key protein for the control of cholesterol transport in vivo, plays an important role in inhibition cholesterol synthesis and conversion of excess cholesterol to bile acids [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Results from recent studies have implicated that activation of Peroxisome proliferator-activated receptors associated with the regulation of lipid metabolism and alleviation of inflammation triggers hypolipidemic activities via acting on gene expression involved in lipid homeostasis [19] . There is emerging evidence that PPARα, a positive regulator of lipolysis connected with fatty acid oxidation and extracellular lipid metabolism, has ability to regulate the lipolysis of very low-density lipoproteintriglycerides (VLDL-TG), thereby raising plasma HDL-C levels and decreasing the levels of LDL-C and TG [19,20] . On the other hand, CYP7A1, as a key protein for the control of cholesterol transport in vivo, plays an important role in inhibition cholesterol synthesis and conversion of excess cholesterol to bile acids [21] .…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway enrichment analysis showed that PPAR signaling pathway was significantly enriched by the DEGs ACOX2, SCD5, CPT1A, PPARα, ACOX1, RXRB, PCK2, SLC27A5, CPT2, EHHADH and RXRA, playing key roles in the regulation of multiple types of cells metabolism process. As a key member of this pathway, PPARα is involved in lipid metabolism in the liver and muscle, and is a key regulator of hepatocytes growth and metabolism; it has been demonstrated that PPARα could be utilized as a candidate gene for marker-assisted selection for growth in cattle 48 – 50 . CPT1A gene is reported to be involved in regulating the growth traits in goat 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in PPARs genes have been linked to growth, development, and meat quality in various species such as cattle and sheep [15][16][17]. A 636A>G SNP in the PPARα gene influenced adipose accumulation in Polish landrace pigs [18].…”
Section: Introductionmentioning
confidence: 99%